Sulfidation of ZIF-Derived Core-Shell NiCo LDH/Ni MOF Heterostructure toward Supercapacitor Electrodes with Enhanced Performance - Xin Zheng; Yihui Sun; Sijia Jin; Minxuan Xu; Yanyan Ding; Fei Chen; Tao Yang; Qi Zhang; Xinyue Zheng; Hao Chen (Batteries, 2022)
Developing electrodes in a reasonable structure is essential to boost the performance of supercapacitors. Self-supporting heterostructures enriched active sites are promising as binder-free electrodes for supercapacitors. Here, core-shell layered double hydroxide (LDH)/Metal organic frame (MOF) heterostructure was directly grown on carbon cloth (CC) substrate derived from L-Co ZIF NWAs. Subsequently, the composite was treated with a sulfidation process to optimize its electrical conductivity. Thanks to its unique network structure, it facilitates active site exposure and efficient charge transfer, together with the synergetic effect between NiCo double hydroxide and Ni MOF nanosheets. This hybrid electrode possesses an excellent specific capacity (1200 F g−1 at 1 A g−1) and stable cycle performance with 86% capacity maintained after 4000 cycles, indicating its potential superiority for use in high-efficiency electrochemical capacitors.